PENGEMBANGAN E-MODUL BERBASIS HEYZINE FLIPBOOK MATERI SISTEM PENCERNAAN MANUSIA - Aulia Rahmadani Fitri; Putri Octa Hadiyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop and describe the feasibility of an interactive electronic module (e-module) based on Heyzine Flipbook on the topic of the human digestive system for fifth-grade students at SD Negeri 21 Pekanbaru. The background of this study is that Natural and Social Sciences (IPAS) learning still relies on printed textbooks and worksheets that cannot present abstract material dynamically, so that students find it difficult to understand the digestive system topic and lose motivation to learn. This research applies the Research and Development (R&D) method using the ADDIE model, limited to three stages, namely Analysis, Design, and Development. The e-module was designed with Canva and converted into an interactive flipbook using Heyzine Flipbook, then validated by six experts (media, language, and content) and tried out on one teacher and 28 fifth-grade students. The results show that the media validation reached 93%, language validation 95%, and content validation 96%, all categorized as "very valid". The teacher response reached 95% and the student response reached 93%, both categorized as "very appropriate", with an overall average of 94.4%. These findings indicate that the Heyzine Flipbook-based e-module is valid, practical, and appropriate for use as a digital teaching material in IPAS learning on the human digestive system.